1996
DOI: 10.1161/01.atv.16.7.851
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Morphology Classification of the Arterial Wall and Cardiovascular Events in a 6-Year Follow-up Study

Abstract: A 6-year follow-up based on an arterial morphology classification defined with an ultrasound assessment of carotid and femoral artery bifurcations was conducted on 2322 asymptomatic subjects. Four morphology classes were considered. When 2000 subjects (86% of total subjects; 1124 males, 876 females) completed a 6-year follow-up, the study was terminated. At 6 years, no cardiovascular events were observed in subjects who were in class I (80.05% of the population sample) at inclusion; there were 69 events in cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 19 publications
0
102
0
6
Order By: Relevance
“…[5][6][7][8][9][10][11][12]20 Compared with carotid IMT and the AAI, the presence and severity of carotid plaques or aortic atherosclerosis are less frequently studied in relation to cardiovascular disease. Importantly, the present study shows that the hazard ratios for MI for these measures, which are based on the relatively crude but direct assessment of the presence of atherosclerotic plaques, were as high as those for carotid IMT, a measure that requires very precise measurements.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12]20 Compared with carotid IMT and the AAI, the presence and severity of carotid plaques or aortic atherosclerosis are less frequently studied in relation to cardiovascular disease. Importantly, the present study shows that the hazard ratios for MI for these measures, which are based on the relatively crude but direct assessment of the presence of atherosclerotic plaques, were as high as those for carotid IMT, a measure that requires very precise measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early atherosclerotic lesions involving only the intimal layer may cause only small increases in the composite wall thickness measured by vascular ultrasonography that might be confused with medial hypertrophy in the presence of hypertension. Although this could be a major limitation of ultrasonographic studies of preclinical atherosclerosis, the consistent ability of increased IMT to predict cardiovascular events in multiple populations [11][12][13][14][15] suggests that the different processes that increase overall carotid wall thickness are all prognostically adverse. Furthermore, since the atherosclerotic process typically involves the arterial wall in a focal fashion, whereas hypertension induces diffuse thickening of the intimal-medial complex, 46 ultrasonographic identification of focal intimal-medial thickening can be considered a reliable indicator of atherosclerosis per se.…”
Section: Saba Et Al Carotid Structure In Hypercholesterolemic Hypertementioning
confidence: 99%
“…Previous reports have indicated that carotid intimal-medial thickening is associated with coronary artery disease 9,10 and cardiovascular morbidity and mortality. [11][12][13][14][15] Moreover, carotid intimalmedial thickening has been described in association with hypertension 16,17 and hypercholesterolemia. 18,19 Studies of hypercholesterolemia have, however, included subjects with mild hypertension and/or symptomatic cardiovascular disease, and thus, they could not assess the independent contributions of uncomplicated hypertension and hypercholesterolemia to intimal-medial thickening.…”
mentioning
confidence: 99%
“…Thus, it may be difficult to use the IMT as an exact normative value. In addition, we cannot demonstrate the prevalence of carotid artery plaque formation, which is a strong predictor of cardiovascular diseases [19,29,30].…”
Section: Discussionmentioning
confidence: 88%